How to observe business operations: An empirical study of family business. - Tsu-Cheng Chou; Hsi-Peng Lu (PLoS ONE, 2022)
The direct observation method is commonly used for data collection in family business case studies. Nevertheless, in research on family business succession that is mainly based on retrospective data, it is difficult to directly observe an event or situation at a given time. This paper thus first explores the application of observation data in the published research results of some family business case studies through a literature review. It then describes our observation methodology, i.e., sampling process, method, observation process, and reevaluation of our interview data, through a case study. Finally, the conclusion offers suggestions for using these observation methods, i.e., employing different types of observation, by considering running time and financial cost, familiarizing observers with various observation occasions, and seeking the assistance of relevant professionals for a research topic.